Promoting psychological resilience in the U.S. military - Meredith, Lisa S., 1959- (Rand Corporation monograph series, 2011)
As U.S. service members deploy for extended periods on a repeated basis, their ability to cope with the stress of deployment may be challenged. A growing number of programs and strategies provided by the military and civilian sectors are available to encourage and support psychological resilience to stress for service members and families. Though previous research from the field of psychology delineating the factors that foster psychological resilience is available, there has been no assessment of whether and how well the current military resilience programs are addressing these factors in their activities. Further, little is known about the effectiveness of these programs on developing resilience. To assist the Department of Defense in understanding methodologies that could be useful in promoting resilience among service members and their families, the authors conducted a focused literature review to identify evidence-informed factors for promoting psychological resilience. The study also reviewed a subset of military resilience programs to determine the extent to which they included those evidence-informed factors. This report describes the context, approach, and findings from these research activities.